Is the Teisseyre‐Tornquist Zone an ancient plate boundary of Baltica?. Issue 12 (16th December 2015) - Mazur, Stanislaw; Mikolajczak, Mateusz; Krzywiec, Piotr; Malinowski, Michal; Buffenmyer, Vinton; Lewandowski, Marek
Abstract: The Teisseyre‐Tornquist Zone (TTZ) is generally regarded as a fossil plate boundary in Europe that extends 2000 km from the Baltic Sea to the Black Sea. We used an integrated approach merging potential fields and seismic data to explore crustal architecture across the TTZ in central Poland. The aim of the study was to test whether the TTZ coincides with an early Paleozoic (Caledonian) suture formed through the closure of the Tornquist Ocean along the SW Baltica margin. The suture is presumed to separate the East European Craton (EEC) from the Paleozoic terranes of Western Europe. Two seismic reflection lines from the PolandSPAN™ experiment were used to image the deep structure at the SW margin of the EEC. Lines PL‐5300 and PL‐5400 run NE‐SW in central and northern Poland, respectively. The seismic interpretation down to top of basement was integrated with 2‐D gravity and magnetic modeling to highlight the structure of the deep crust. Both the gravity and magnetic models show a suture that welds together two blocks at the base of crust. However, top of basement above the suture dips uniformly to the SW and is overlain by undisturbed lower Paleozoic and younger sediments. By implication, the suture must have developed in the Precambrian and both crustal blocks amalgamated belong to the EEC. Consequently, the Caledonian suture, formed by the closure of the Tornquist Ocean between Avalonia and Baltica, must be located farther southwest beneath thick upper Paleozoic and Mesozoic sediments. Key Points: Seismic and potential fields data are integrated to study crustal structure Teisseyre‐Tornquist Zone is not a suture formed by Baltica‐Avalonia docking Crustal architecture is nonunique and can be produced by combination of various tectonic processes